PERFORMANCE EVALUATION BETWEEN TWO AUTOMATED BIOCHEMICAL ANALYZER SYSTEMS: ROCHE COBAS 8000 AND MINDRAY BS2000M: Evaluated performance of Roche Cobas 8000 and Mindray BS2000M - Chen, Mingxing; Qin, Simeng; Yang, Sitao; Chen, Huaping; Lu, Liuyi; Qin, Xue (Journal of Medical Biochemistry, 2021)
Summary Background. The values of biomarkers play a central role in routine clinical decision-making. Whereas, the performances of different automated chemical analyzers remain unclear. To determine the performances of different platforms, we evaluated the capability between Roche Cobas 8000 and Mindray BS2000M. Methods. A total of 1869 remaining serum samples were collected. CK, LDH-1, RBP, Cys-c, IgA, IgM and IgG were assessed by using paired-t test, Passing-Bablok regression analysis and Bland Altman analysis according to CLSI EP5-A3. Results. There were significant in average bias of all items between two machines (P < 0.001). Due to the 95% confidence interval of intercept A included 0, CK, LDH-1, Cys-c and IgG were not show systemic error in Passing-Bablok regression analysis. Except for IgA, the r values and correlation coefficient of all items were higher than 0.91, which showed that the correlation and consistency is good. The Bland-Altman analysis showed that two instruments had more than 95% of the points apart from CK, LDH-1, and IgA. Conclusions. It can be considered that the two instruments have good correlation and consistency in CK, LDH-1, RBP, Cys-c, IgM and IgG, and the two instruments are interchangeable and can replace each other.